2014
DOI: 10.1155/2014/163074
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Reactions of Five-Membered Heterocycles Using Phase Transfer Catalyst (PTC) Techniques

Abstract: Phase transfer catalysts (PTCs) have been widely used for the synthesis of organic compounds particularly in both liquid-liquid and solid-liquid heterogeneous reaction mixtures. They are known to accelerate reaction rates by facilitating formation of interphase transfer of species and making reactions between reagents in two immiscible phases possible. Application of PTC instead of traditional technologies for industrial processes of organic synthesis provides substantial benefits for the environment. On the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…In our study, the reaction was carried out with ethyl chloroacetate in the presence of potassium carbonate and a small amount of quaternary ammonium (tetrabutylammonium acid sulphate) as a phase transfer catalyst. Potassium carbonate is used to deprotonate the hydroxyl functions of the starting product [30] while quaternary ammonium is used to perform solid/liquid phase transfer [31]. Ethyl chloroacetate is used both as a reagent and as a solvent, so we put it in excess of 10 mol/mol.…”
Section: Oxyacetic Acid Of Anacardic Acid (5) Synthesis With Ethyl Ch...mentioning
confidence: 99%
“…In our study, the reaction was carried out with ethyl chloroacetate in the presence of potassium carbonate and a small amount of quaternary ammonium (tetrabutylammonium acid sulphate) as a phase transfer catalyst. Potassium carbonate is used to deprotonate the hydroxyl functions of the starting product [30] while quaternary ammonium is used to perform solid/liquid phase transfer [31]. Ethyl chloroacetate is used both as a reagent and as a solvent, so we put it in excess of 10 mol/mol.…”
Section: Oxyacetic Acid Of Anacardic Acid (5) Synthesis With Ethyl Ch...mentioning
confidence: 99%
“…However, from a practical standpoint, their high cost and toxicity were limitations for their application to our purposes. Consequently, we evaluated several PEGs and quaternary ammonium salts as PTCs for the N-alkylation of 1,2,4-triazole 14- 15 . The relative catalytic effi ciency of each is displayed in Table 2, revealing the highest conversion rate for PEG-1000.…”
Section: The Selection Of Phase-transfer Catalystmentioning
confidence: 99%
“…As a consequence, reaction rates have been accelerated. 30,31 economic and environmental benefits for commercial organic synthesis operations. Many studies have shown that PTC is the most efficient approach to produce a large number of active intermediates.…”
Section: ■ Introductionmentioning
confidence: 99%